MODEL PEMBELAJARAN INOVATIF DALAM PAI (KONSEP DAN MACAM-MACAM MODEL PEMBELAJARAN INOVATIF DALAM PAI) - Rika, Rika; Rainatul Agustina, Nadya; Cahyadi, Ani (Berajah Journal, 2024)
Learning that uses creative new methods and prioritizes critical thinking, active involvement and active participation of students in the learning process. This learning model aims to develop students' ability to think independently, creatively and innovatively, so that they can generate new ideas, solve problems and apply knowledge in real life. From this background, the aim of this research is to provide an explanation of innovative learning models in PAI (concepts and various types of innovative learning models in PAI). This research is a type of library research (Library Research) which uses a qualitative approach with descriptive methods, the data collection technique is a literature study, and the data analysis uses the content analysis method (Content Analysis). The results of the research show that the existence of an innovative learning model that can be applied when learning PAI will create motivation to learn PAI, whereas initially learning PAI was monotonous with conventional models only in the classroom, for example by using the CTL model, PAI learning can be carried out outside the classroom. , the effect of which will provide an interesting impression when PAI learning is carried out, because students are given more freedom to express themselves. In this case, there are several types of innovative learning models in Islamic Religious Education, namely: Discovery Learning, Problem-Based Learning (PBL), Problem Solving, Contextual, PAIKEM, and Cooperative.